Pengaruh Kepercayaan Dan Keamanan Layanan Digital Payment Terhadap Keputusan Bertransaksi Online (Studi Pada Mahasiswa Universitas Muhammadiyah Mataram) - Ningtias, Karmelia Sasmita; Yunarni, Baiq Reinelda Tri; Indra, Nurul Hidayati (Universitas Hamzanwadi, 2025)
This study examines the influence of trust and security of Digital Payment services on transaction decisions of students at the University of Muhammadiyah Mataram. This research is quantitative with a sample of 99 students at the University of Muhammadiyah Mataram. Data collection using questionnaires. The analysis method used is multiple linear regression to assess the impact of trust and security on students' transaction decisions. The purpose of this study is to determine partially and simultaneously the trust and security of Digital Payment services on Online transaction decisions of students at the University of Muhammadiyah Mataram. The results of this study indicate that 1) trust in Digital Payment services has a significant influence on Online transaction decisions of students at the University of Muhammadiyah Mataram. 2) security in Digital Payment services has a significant influence on Online transaction decisions of students at the University of Muhammadiyah Mataram, and 3) Trust and security in Digital Payment services have a simultaneous influence on Online transaction decisions of students at the University of Muhammadiyah Mataram